Reinforced carbon fiber laminates with oriented carbon nanotube epoxy nanocomposites: Magnetic field assisted alignment and cryogenic temperature mechanical properties - He, Yuxin; Yang, Song; Liu, Hu; Shao, Qian; Chen, Qiuyu; Lu, Chang; Jiang, Yuanli; Liu, Chuntai; Guo, Zhanhu (Journal of colloid and interface science, 2018)
[Display omitted] The epoxy nanocomposites with ordered multi-walled carbon nanotubes (MWCNTs) were used to influence the micro-cracks resistance of carbon fiber reinforced epoxy (CF/EP) laminate at 77 K, Oxidized MWCNTs functionalized with Fe3O4 (Fe3O4/O-MWCNTs) with good magnetic properties were prepared by co-precipitation method and used to modify epoxy (EP) for cryogenic applications. Fe3O4/O-MWCNTs reinforced carbon fiber epoxy composites were also prepared through vacuum-assisted resin transfer molding (VARTM). The ordered Fe3O4/O-MWCNTs were observed to have effectively improved the mechanical properties of epoxy (EP) matrix at 77 K and reduce the coefficient of thermal expansion (CTE) of EP matrix. The ordered Fe3O4/O-MWCNTs also obviously improved the micro-cracks resistance of CF/EP composites at 77 K. Compared to neat EP, the CTE of ordered Fe3O4/O-MWCNTs modified CF/EP composites was decreased 37.6%. Compared to CF/EP composites, the micro-cracks density of ordered Fe3O4/O-MWCNTs modified CF/EP composites at 77 K was decreased 37.2%.